PENGARUH METODE GUIDED READING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V DI SD NEGERI 105288 SEI ROTAN - Realita Purba; Fahrur Rozi; Eva Betty Simanjuntak; Halimatussakdiah; Edizal Hatmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of the Guided Reading method on the reading comprehension skills of fifth-grade students at SD Negeri 105288 Sei Rotan. This research employed a quantitative approach with a Pre-Experimental Design in the form of a One Group Pretest-Posttest Design. The research subjects consisted of 34 students selected using a saturated sampling technique. Data were collected through tests, observations, and documentation. The research instrument was tested through validity, reliability, difficulty level, and discrimination index tests. The data were analyzed using the Shapiro-Wilk normality test and Paired Sample t-Test hypothesis testing with the assistance of IBM SPSS Statistics.The results showed an improvement in students’ reading comprehension skills after the implementation of the Guided Reading method. The average pretest score of 62.12 increased to 85.15 in the posttest, with an improvement of 23.03 points. The minimum score increased from 50 to 76, and the maximum score increased from 75 to 94. The normality test results showed that the data were normally distributed, with significance values of 0.432 for the pretest and 0.179 for the posttest (> 0.05). The results of the Paired Sample t-Test showed a Sig. (2-tailed) value of 0.000 < 0.05 and a t-count value of 58.653 > t-table 2.034, indicating that H₀ was rejected and Hₐ was accepted. Therefore, the Guided Reading method has a significant effect on improving the reading comprehension skills of fifth-grade students at SD Negeri 105288 Sei Rotan.